Perubahan Warna Pada Bahan Restorasi Resin Komposit Nanofiller Terhadap Perendaman Saliva Buatan Dengan pH 5 - Widyastuti, Wiena; Tri Septiani, Afifa (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Background: The high level of public awareness regarding aesthetic values influences the evolution and selection of restoration materials. Nanofiller composite resin is an option in aesthetic restoration because it has good aesthetic qualities, mechanical properties and high wear resistance. Color changes that occur in nanofiller composite resin are undesirable because they disturb the aesthetic value and appearance. Color changes in restoration materials are influenced by the acidic pH contained in artificial saliva. Objective: This study aims to determine the effect of artificial saliva with a pH of 5 on the color change of nanofiller composite resin restoration materials. Methods: The research object is a nanofiller composite resin with a diameter of 10 mm, and a thickness of 2mm. The research was carried out by soaking nanofiller composite resin in artificial saliva and distilled water solution. The study was divided into 2 groups, namely the treatment group and the control group. Which is placed in an incubator at a temperature of 37˚ C for 24 hours. In the control group, samples were soaked in distilled water for 24 hours, and repeated for 7 days. In the treatment group, samples were soaked in artificial saliva for 4 hours, repeated for 7 days, followed by immersion in distilled water. The color parameters of the research subjects were measured using a Vita Easyshade V spectrophotometer before and after immersion in the control and treatment groups on the 7th day. The measurement results data after carrying out the normality test, T-test (dependent), and Wilcoxon test. Results: The results of this study showed a significant color change (p<0.05). Conclusion: There is an effect of artificial saliva with a pH of 5 on the color change of the nanofiller composite resin material.